2009
DOI: 10.1089/ten.tea.2008.0594
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Nanoporous Anodic Aluminium Oxide Membranes to Influence Skin Wound Repair

Abstract: Cells respond to changes in the environment by altering their phenotype. The ability to influence cell behavior by modifying their environment provides an opportunity for therapeutic application, for example, to promote faster wound healing in response to skin injury. Here, we have modified the preparation of an aluminium oxide template to generate large uniform membranes with differing nano-pore sizes. Epidermal cells (keratinocytes) and dermal cells (fibroblasts) readily adhere to these nanoporous membranes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 45 publications
0
39
0
Order By: Relevance
“…Our group has demonstrated that the topographic cues intrinsic to the native BM [7], unequivocally influence wound healing behaviors [1820]. Parkinson et al demonstrated that the size of nano-pores on aluminum oxide membranes influenced the rate of keratocyte proliferation and migration in vitro [29]. In addition, the use of topographically patterned membranes as dressings lead to less granulation tissue and a more mature epidermal layer in skin than control standard burn dressings in vivo [30].…”
Section: Discussionmentioning
confidence: 99%
“…Our group has demonstrated that the topographic cues intrinsic to the native BM [7], unequivocally influence wound healing behaviors [1820]. Parkinson et al demonstrated that the size of nano-pores on aluminum oxide membranes influenced the rate of keratocyte proliferation and migration in vitro [29]. In addition, the use of topographically patterned membranes as dressings lead to less granulation tissue and a more mature epidermal layer in skin than control standard burn dressings in vivo [30].…”
Section: Discussionmentioning
confidence: 99%
“…13 Representative SEM images of each of the prepared membranes are shown in Figure 1. Pore geometry was analyzed using SPIP software over full SEM micrographs and also within ordered pore domains.…”
Section: Anodic Aluminum Oxide Membranesmentioning
confidence: 99%
“…13 Preliminary experiments showed that keratinocytes adhered to the membranes and were sensitive to nano-scale changes in topography. In this work, detailed studies of cell phenotype on the nanoporous membranes are presented and discussed with an optimal pore size determined for application in vivo.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the surface chemistry and topography of a potential material for use with cells must be biologically compatible for this substrate to induce productive cell-material interactions. In the case of AAO membranes, the unique surface properties have been investigated by a number of researchers for a number of cells such as keratinocytes and fibroblasts [17], hepatocytes [18], endothelial and vascular smooth muscle cell [19], and osteoblasts [20]. The results of these studies all confirm the importance of addressing the behaviour of a specific cell line to the scaffold environment.…”
Section: Introductionmentioning
confidence: 92%